MID1 inhibitors to delay disease progression in neurodegenerative diseases - Baski, Nahawand (My University, 2024)
Neurodegenerative diseases (NDs) are characterized by neuronal damage where nerve cells degenerate and die. Alzheimer’s and Parkinson’s diseases are the most prevalent and well-known NDs. Current treatments alleviate the symptoms but are unable to slow the progression of the disease or the destruction of the nerve cells. Therefore, finding novel therapies that could modify the course of neurodegenerative diseases is important. Midline 1 (MID1), a ubiquitin ligase, is a novel potential target for drug development. The protein forms a complex with protein phosphatase 2A (PP2A) and its subunit α4 and transports them to proteasomes for degradation. MID1-inhibitors aim to prevent the degradation of MID1- α4- PP2Ac complex in proteasomes and thus increase the PP2A protein activity in cells. Through this, tau is dephosphorylated and stabilized in microtubules as PP2A is the main phosphatase to dephosphorylate tau. Tau protein dephosphorylation promotes normal cell metabolism and maintains cell structure of microtubules, preventing cell malfunction and synaptic impairment. This also prevents the formation of the toxic neurofibrillary tangles that damage neurons, and thus the progression of the disease. The purpose of the study was to characterize MID1 as a drug target for small-molecule inhibitors and study how the MID1 modification affects PP2A levels and MID1-α4 -interaction. The research included MID1 validation and compound testing done at the same time. The experiment started with the validation of MID1 as a drug target. The aim was to silence MID1 from human embryonic kidney 293 cells by using commercial MID1 small interfering RNA (siRNA). Although the results obtained were not statistically significant, the association between MID1 and PP2A is noticeable with the MolPort 6 inhibitor compound. Key words: Neurodegenerative diseases, MID1-α4-PP2Ac complex, MID1-inhibitors.
Keywords: Neurodegenerative diseases, MID1-α4-PP2Ac complex, MID1-inhibitors